Analisis Kewajiban dan Perlindungan Konsumen Dalam Kontrak Jual Beli - Putri, Alitha Sulistyo; Kirani, Marsyah; Sadi, Multias Febriana; Setiawan, Raniya Qanita; S, Surahmad (Media Hukum Indonesia (MHI), 2024)
This study discusses consumer obligations and protection in sales and purchase contracts which are an integral part of the legal relationship between sellers and buyers. In sales and purchase transactions, consumers are often in a weaker position compared to sellers, both in terms of information and the ability to negotiate the terms of the contract. Therefore, the law provides special protection for consumers to guarantee their rights, including guarantees for purchased products, the right to correct information, and the right to compensation in the event of losses due to defective products or products that do not comply with the agreement. This study analyzes various legal aspects that regulate seller obligations, such as the obligation to provide products that are suitable and in accordance with the description, and the obligation not to mislead consumers. In addition, this study also evaluates the role of consumer protection laws in Indonesia in protecting consumer rights, with a focus on Law No. 8 of 1999 concerning Consumer Protection. The research method used is normative juridical with a statutory regulatory approach and case studies. The results of the study indicate that the Consumer Protection Law is effective in protecting consumer rights bound by sales and purchase contracts.